Reasons for non-participation of children and adolescents in a large-scale school-based mental health project - Baldofski, Sabrina; Klemm, Sarah-Lena; Kohls, Elisabeth; Mueller, Sophia M. E.; Bauer, Stephanie; Becker, Katja; Diestelkamp, Silke; Eschenbeck, Heike; Hiery, Alisa; Kaess, Michael; Koenig, Julian; Lehner, Laya; et al. (Frontiers in Public Health, 2024)
interests. KB has received honorary from Georg Thieme Publisher during the last five years outside and independent of the submitted work. CR-K received lecture honoraria from Recordati and Servier outside and independent of the submitted work.SaB and SLK equally contributed to the current paper and share first authorship. SaB, EK, and CR-K designed the study and constructed the questionnaire. SaB performed the statistical analysis and SMEM performed the qualitative analysis. SaB, SLK, and EK drafted the article.